Sleep changes during a spontaneous manic episode: PSG assessment in a clinical context. (May 2023) - Pacchioni, F; Cavallini, M.C.; Fregna, L.; Casoni, F.; Sarzetto, A.; Attanasio, F.; Barbini, B.; Locatelli, M.; Colombo, C
Highlights: PSG is a reliable and safe tool that allows the precise quantification of night rest and to evaluate its architecture. Changes in sleep architecture appear to be sensitive markers of clinical changes during a manic episode of bipolar disorder. Sleep management during the manic episode is confirmed as a primary clinical objective. Abstract: Sleep plays a key role in the pathogenesis and clinical presentation of mood disorders. However, only a few studies have investigated sleep architecture during the manic episodes of Bipolar Disorder (BD) and changes in sleep parameters that follow clinical variations. Twenty-one patients (8 males, 13 females) affected by BD, manic phase, underwent polysomnographic recordings (PSG) at the beginning of the admission in our ward (T0 ) and after three weeks of hospital treatment (T1 ). All participants were clinically evaluated using Young Mania Rating Scale (YMRS), Pittsburgh Sleep Quality Index (PSQI) and Morningness-Eveningness Questionnaire (MEQ). During the admission, we observed an increase in both quantity (Total Sleep Time - TST) and quality (Sleep Efficiency - SE) of sleep. In addition, clinical improvement, evaluated with YMRS and PSQI scales, was accompanied by a significant increase in the percentage of REM sleep. According to our findings, the improvement of manic symptoms is accompanied by an increase in "REM pressure" (increase in REM% and REM density, reduction of REM latency). Overall, changes in sleep architecture appear to be markers sensitive to clinical variations during manic phases of Bipolar Disorder.